MiR-130a-3p Alleviates Inflammatory and Fibrotic Phases of Pulmonary Fibrosis Through Proinflammatory Factor TNF-α and Profibrogenic Receptor TGF-βRII - Ding, Yan; Hou, Yapeng; Liu, Yanhong; Yu, Tong; Cui, Yong; Nie, Hongguang (Frontiers in Pharmacology, 2022)
Pulmonary fibrosis (PF) is a progressive disease characterized by extracellular matrix (ECM) deposition that destroys the normal structure of the lung parenchyma, which is classified into two successive inflammatory and fibrotic phases. To investigate the anti‑inflammatory and anti‑fibrotic roles of miR-130a-3p on mice with bleomycin (BLM)-induced PF and the underlying mechanism, we performed single-cell RNA sequencing analysis, which demonstrated BLM increased/decreased the percentage of macrophages and fibroblasts/epithelial cells in PF lungs, respectively. The differentially expressed genes were enriched in PPAR signaling pathway and lysosome, ECM-receptor interaction and ribosome, and metabolism reaction. Time-course studies demonstrated that the inflammation related factors increased significantly at day 7 (inflammatory phase), whereas the fibrosis related factors increased at day 28 (fibrotic phase) after BLM exposure. Meanwhile, miR-130a-3p could ameliorate pulmonary lesions by downregulating the secretion of inflammatory cytokines (IL-1β, IL-6, TNF-α, TGF-β1) and the deposition of ECM (α-SMA, FN, HYP, Collagen) in the inflammatory and fibrotic phase, respectively. In LPS induced inflammatory cell model, the upregulation of miR-130a-3p was mainly achieved by the activation of NF-κB signaling pathway, which suppressed the proinflammatory factor TNF-α. Comparatively, TGF-β/Smad signaling pathway was inhibited by miR-130a-3p targeting TGF-βRII in TGF-β1 deduced fibrotic cell model. The evidence supports that miR-130a-3p exerts an anti-inflammatory and anti-fibrotic effect in BLM-induced PF, implying a potential pharmacological agent in the therapy of PF patients.